Community care for severely frail older people: Developing explanations of how, why and for whom it works. (27th December 2018) - Lhussier, Monique; Dalkin, Sonia; Hetherington, Ross
Abstract: Background: A Community Wellness Team was implemented in North East England in 2014, in line with national policy directives to support frail older people in the community. The service provides a comprehensive and integrated care package, which aims to reduce avoidable admissions, inappropriate service use and enable patients to stay at home. Design: A realist design combining a review of the literature and primary data collection from service providers and patients was used to develop programme theories explaining the links between the Team interventions and expected outcomes. Results: Five programme theories were developed, detailing: trust development and relationship building; risk minimisation in the home environment; advice on self‐management; referral to preventative services; and coordination of services. Discussion: The programme theories explain the role and impact of the Community Wellness Team. These programme theories are interrelated and impact one another; a hypothesised progression of programme theories indicating how the Community Wellness Team "works" is discussed. Of particular importance was the comprehensive initial assessment, which leads to the alteration of the social and physical environment within which older people live. Conclusion: Severely frail older people present cases that are complex socially, medically, financially and environmentally. In order to meet these needs, the Team coordinators are adopting a complex and flexible person‐centred approach. Implications for Practice: This study paves the way for further research into the care networks surrounding severely frail older people living in the community, and how they can most effectively be implemented.